AI-Driven Cyber Threat Intelligence as a Management Information System: Integrating Cybersecurity Governance and IT Project Management for Organizational Resilience - Shuchona Malek Orthi; Partha Chakraborty; Md Abubokor Siam; Ahmed Shan-A-Alahi; Abdullah Al Zaiem; Syed Nazmul Hasan; Jobanpreet Kaur; Foysal Mahmud; Mohammad Abdul Goffer (The Eastasouth Journal of Information System and Computer Science, 2023)
As organizations quickly become increasingly digital, they are experiencing escalating, complex cyber threats. These challenges make cybersecurity an important area for managers and governance, and not just a technical problem. Even if you are a heavy investor in security tech, it still happens to many companies to suffer from cyber. The reasons are broken information flows, a lack of clear visibility among managers, and misalignment between the security operations and the overall decision-making. This research rethinks Artificial Intelligence (AI) based Cyber Threat Intelligence (CTI) as a Management Information System (MIS). It combines the approach of cybersecurity governance and IT project management to increase the resilience of organizations. Using MIS theory, cybersecurity governance models, and studies of IT project management, the paper derives one cohesive model for translating raw threat data into useful managerial insight. Through a design science methodology, the research chooses a lot of scholarly sources and demonstrates a layered AI-enabled CTI-MIS architecture. This is good architecture for strategic oversight, risk-based governance, and flexible project execution. The paper extends the theory of MIS to Artificial Intelligence (AI) driven cybersecurity intelligence and provides practical knowledge for companies seeking to achieve resilient digital transformation in a time of evolving cyber threats.